The effectiveness of a development of salt diet restriction program to delay the progression of chronic kidney disease in Bangrakam District - Boonyanupapong, Jedsada; Prompakdee, Ratchaya (Journal of Preventive Medicine Association of Thailand, 2021)
This quasi-experimental research (nonequivalent control group pretest-posttest design) aimed to study and compared health behavior of salt diet, knowledge of chronic kidney disease, clinical outcome including glomerular filtration rates, blood pressure, urine microalbumin and measured the salt level in food. The sample population was patients of chronic kidney disease stage 3 total of 40 participants. The experimental group participated in the salt diet restriction program in addition to usual care. The control group received only usual care. The data collection was a survey questionnaire including knowledge and behavior assessment, salinity meter PPM/TDS. The duration of the research was 25 weeks. The data were analyzed using descriptive statistics chi-square test and independent t-test. The results are the mean score of salt diet behavior and knowledge of chronic kidney disease in the experimental group after getting a salt restriction program is higher than the control group with a significant statistical level at the level 0.05. The mean score of clinical outcomes in the experimental group, including glomerular filtration rates increased, while urine microalbumin level and salt level in food decreased significantly at the level of 0.05. This research pointed out that salt diet restriction program was effective way to enhance knowledge and appropriate salt diet restriction behavior that will lead to delay the progression of chronic kidney disease in long term care.